Contramemoria. Historia, genealogía y ontología del presente en Michel Foucault / Counter-Memory. History, Genealogy and Ontology of the Present in Michel Foucault - López Alcañiz, Vladimir (Historiografías, 2017)
El territorio de la memoria se ha expandido entre la década de los sesenta y los años de los “aniversarios alemanes”. La frontera con los dominios de la historia se vuelve porosa y muchos pretenden redibujarla. En ese contexto emerge la figura de Michel Foucault. De su mano recorremos el malestar en la cultura y las ansiedades que genera la pérdida de la tradición. Su genealogía responde a ese malestar y rastrea las discontinuidades del tiempo a modo de contramemoria que disuelve la quimera del origen y levanta la máscara de las identidades. Su meta, lograr una ontología del presente que haga de la historia un instrumento indispensable de la crítica.Palabras claveMichel Foucault, genealogía, historia efectiva, ontología del presente, contramemoria. AbstractThe territory of memory has been expanding from the sixties to the years of the so-called German anniversaries. The border with the field of history becomes porous and many scholars seek to redraw it. In this context the figure of Michel Foucault emerges. With his aid, we shall focus on culture and its discontents and on anxieties generated by the loss of tradition. Foucault’s genealogy corresponds to such discontent and traces the discontinuities of time, that viewpoint understood as a counter-memory which dissolves the chimera of the origin and lifts the mask of identity. Its goal is attaining to an ontology of the present that makes the history writing an indispensable instrument of the critique.Key WordsMichel Foucault, genealogy, effective history, ontology of the present, counter-memory.